Quality assessment of squash (Cucurbita maxima) noodles with malunggay (Moringa oleifera) processed in Brgy. Esparar, Barbaza, Antique - Villaram, Mark Christian Bianson
The squash noodles with malunggay (SNM) locally processed in Brgy. Esparar, Barbaza, Antique was subjected to physical, physico-chemical tests (aw determination, proximate analysis, determination of free fatty acid value and peroxide value) microbiological tests (Total Plate Count, Yeast and Molds Count and E. coli detection) and sensory evaluation, to establish the quality of the product.